Coordination between upper- and lower-limb movements is different during overground and treadmill walking - Carpinella, I.; Crenna, P.; Rabuffetti, M.; Ferrarin, M. (European Journal of Applied Physiology, 2010)
Locomotion studies employ either treadmill (TW) or overground walking (OW), considering that differences between them are negligible. The present study tests this notion by comparing coordination between upper- and lower-limb movements in healthy individuals during OW and TW at matched speeds. Results indicated that TW induced a higher cadence, which highly influenced interlimb coordination, in terms of frequency coupling and relative phase between arm and thigh motion. At low speed, the 2:1 pattern (double arm swing per stride) displayed lower incidence in TW compared to OW, and this was correlated with a lower sagittal acceleration at the shoulders, at twice the stride frequency, in the former condition. The low occurrence of the 2:1 coupling in TW, moreover, was correlated to a preferential adoption of a cadence exceeding 80% of the arm`s resonant frequency, whereas higher incidence of this pattern in OW involved a preferential cadence below the 80% threshold. Results indicated also that the relative phase between arm and ipsilateral thigh swinging was smaller in TW, in relation to an earlier occurrence of maximum thigh extension, shortened stance phase, and increased cadence. These findings suggest that arm-leg coordination is different in OW and TW, and that difference can be mainly ascribed to condition-specific setting of central mechanisms for scaling stride frequency, for controlling dynamic axial posture (sagittal shoulder acceleration), and, possibly, for maintaining inter-limb synchrony. Awareness of a different "motor set" in TW and OW is critical if data from the two paradigms are used in physiological and patho-physiological studies.